APPLICATION OF TRAUMEEL S IN THE TREATMENT OF INFLAMMATORY DISEASES OF THE MAXILLOFACIAL REGION - Shokhrukh Shavkat Ugli Mustafokulov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This review article discusses current approaches to the use of Traumeel S in the management of inflammatory diseases of the maxillofacial region, including periodontitis, peri-implantitis, abscesses, and phlegmons. The mechanisms of inflammation and the influence of homeopathic remedies, particularly Traumeel S, on these processes are analyzed. Special attention is paid to the effectiveness of the drug in the postoperative period for reducing edema and pain syndrome, as well as optimizing wound healing. The efficacy of combined treatment using Traumeel S in conjunction with other medications is also considered. In addition, the article presents the results of clinical studies confirming the high effectiveness of this homeopathic preparation in patients with hypersensitivity to conventional pharmaceutical agents.